2023
DOI: 10.1146/annurev-fluid-031822-013213
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of Sessile Droplets

Abstract: The evaporation of a sessile droplet of liquid is a complex and multifaceted fundamental topic of enduring scientific interest that is key to numerous physical and biological processes. As a result, in recent decades a considerable multidisciplinary research effort has been directed toward many different aspects of the problem. This review focuses on some of the insights that can be obtained from relatively simple mathematical models and discusses some of the directions in which the field may move in the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 192 publications
2
49
0
Order By: Relevance
“…There are two principal ways of modeling solvent evaporation in the context of thin evaporating droplets. One is to assume that evaporation is limited by how quickly solvent molecules diffuse away in the surrounding air. This approach requires solving a diffusion equation for the solvent vapor concentration simultaneously with transport equations in the droplet, which is computationally costly. If the droplet is assumed to have a spherical-cap shape, then the computational cost can be greatly reduced, but this simplification cannot describe many important situations where the droplet shape is not a spherical cap.…”
Section: Lubrication Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…There are two principal ways of modeling solvent evaporation in the context of thin evaporating droplets. One is to assume that evaporation is limited by how quickly solvent molecules diffuse away in the surrounding air. This approach requires solving a diffusion equation for the solvent vapor concentration simultaneously with transport equations in the droplet, which is computationally costly. If the droplet is assumed to have a spherical-cap shape, then the computational cost can be greatly reduced, but this simplification cannot describe many important situations where the droplet shape is not a spherical cap.…”
Section: Lubrication Theorymentioning
confidence: 99%
“…The other principal way to model evaporation is to assume that evaporation is limited by how fast solvent molecules leave the liquid phase and enter the vapor phase. , In this approach, the evaporation rate can be determined by solving transport equations only in the liquid phase, not the vapor phase. This results in the so-called one-sided model, where the evaporation flux j e is linearly proportional to deviations of the interfacial temperature and droplet pressure from the saturation temperature and saturation pressure of the solvent.…”
Section: Lubrication Theorymentioning
confidence: 99%
“…3 In this regard, evaporationdriven self-assembly has become an effective method for the controllable patterning of nanoparticles. 4 The pinned contact line of an evaporating sessile droplet induces a capillary flow, which causes liquid from the interior part of the droplet to replenish the escaped mass along the three-phase contact line, 5,6 and the higher evaporation rate near the contact line can also enhance this compensatory flow. 7,8 The evaporation-induced flow inside colloidal droplets can deposit CNTs and align them along the contact line.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-controlled evaporation of sessile droplets is a common occurrence in everyday life, as well as in a myriad of technologically advanced applications [1][2][3]. The ubiquity and significance of this phenomenon have motivated researchers from different fields to examine it in detail.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive list of books and review articles that highlight major contributions to this subject can be found in Ref. [3]. Among recent investigations, the theoretical development of Masoud et al [4] (see also [5]) extended the predictive power of the diffusion-limited model for the evaporation of a single droplet to a broad range of conditions involving multiple drops.…”
Section: Introductionmentioning
confidence: 99%